2k-(k-3)=1(k-51)

Simple and best practice solution for 2k-(k-3)=1(k-51) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-(k-3)=1(k-51) equation:


Simplifying
2k + -1(k + -3) = 1(k + -51)

Reorder the terms:
2k + -1(-3 + k) = 1(k + -51)
2k + (-3 * -1 + k * -1) = 1(k + -51)
2k + (3 + -1k) = 1(k + -51)

Reorder the terms:
3 + 2k + -1k = 1(k + -51)

Combine like terms: 2k + -1k = 1k
3 + 1k = 1(k + -51)

Reorder the terms:
3 + 1k = 1(-51 + k)
3 + 1k = (-51 * 1 + k * 1)
3 + 1k = (-51 + 1k)

Add '-1k' to each side of the equation.
3 + 1k + -1k = -51 + 1k + -1k

Combine like terms: 1k + -1k = 0
3 + 0 = -51 + 1k + -1k
3 = -51 + 1k + -1k

Combine like terms: 1k + -1k = 0
3 = -51 + 0
3 = -51

Solving
3 = -51

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x+7=-3(4-x) | | x^2+8x=-11 | | (3x/4)=(5x+6/2) | | 5(y-2)+1=7y+8 | | (x^2+4x)=0 | | 3(4-5)=52 | | -6(0.1x+0.5)-1.1=-0.5 | | 70=2(15)+2(x+12) | | 7x+9y=3 | | 3+5(2-x)=2(x+4) | | y=19.66666667-7 | | 3-4x=111 | | 9x^2-12x=-5 | | -(1-3x)+4x=-15 | | (14x^2+6x+10)-(2x^2+8)= | | -8(-2m-8)+1=-31+4m | | y=.4x+1.2 | | -5x=-63+2x | | W=F(r+A) | | 1/3x=14 | | 26=5x+10+3x | | y=3+2*3 | | y=3+2*2 | | x/3=-20 | | 3(x+9)=4x-13 | | y=3+2*1 | | y=3+2*0 | | y=3+2*-1 | | y=3+2*-2 | | 4(-1)+y=-7 | | y=2+2*3 | | -22=d/17 |

Equations solver categories